The Sufferings Of Afro-American Maids in Kathryn Stockett's The Help (Journal of the College of Education for Women, 2019)
This research deals with the color bias and its effect on maids in Mississippi in Kathryn Stockett''s (2003) The Help. The ill-treatment and negligence of Afro-American maids received from the white women who employed them in Mississippi that must have affected directly or indirectly on their personality and may eventually lead to suffering. They live in an atmosphere of struggle to free themselves from the complicated relationships between black and white. Afro-American maids pledged to liberate themselves from social oppression by protesting through writing a book which chronicles their stories in slave masters’ homes to make their presence felt as human being equal to their white masters.